Macroeconomic Determinants of Banks' performance in Pakistan - Hashir Ajaz; Faraz Ahmed; Yusra Shehzadi (Institute of Business Management, 2022)
Almost all business operations that are now taking place in the economy may be impacted by recent changes in the macroeconomic indicators of the nation. Thus, the study' s objective was to assess the effect of particular macroeconomic factors on Pakistan' s banking performance. For a period of 13 years, the study tracked data from all active commercial banks in Pakistan (2006-2018). Results were obtained using multiple linear regression and correlation analyses on EViews. According to correlation findings, there was no connection between the exchange rate and NIM or ROE. All other factors,